Understanding On The Management Of Sport Injuries Through Sport Massage And Rice Method For Ipsi Pencaksilat Athletes In Pekalongan District - Mega Widya Putri; Gilang Nuari Panggraita; Idah Tresnowati; Ati safitri; Resty Agustryani (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2021)
The aim of this The aim of this community service is to provide knowledge in the field of handling sports injuries through sports massage and the rice method for pencak silat athletes in Pekalongan Regency theoretically and practically in increasing knowledge of handling sports injuries in the field. This community service is carried out in Pekalongan Regency. The material presented at this seminar is about handling sports injuries through sports massage and the rice method. The results of the implementation of this community service activity are expected to provide knowledge to athletes, especially pencaksilat athletes in Pekalongan Regency and can produce quality masseurs for the recovery needs of athletes in Pekalongan Regency.